Exploring the glass ceiling phenomenon among the recent female medical graduate of Bangladesh (Bangladesh Journal of Medical Education, 2023)
This was a descriptive type of cross sectional study conducted with an objective to find out the unacknowledged barrier to the advancement in medical profession of the recent female medical graduates of Bangladesh. The “glass ceiling” is a metaphor to convey the undefined obstacles that women and minorities face in the workplace.  In this study, a self-administered, semi-structured questionnaire was used for data collection and also In-depth interviews were conducted to gain insight about the cause of drop out and to identify the barrier in academic progression and employment opportunities; along with the possible solution to overcome those obstacles.  In this study, it was revealed that among the (817)recent female medical graduates only 12% were satisfied with their overall employment status while, majority (33.4%) were dissatisfied with their overall employment status. Of which extended work hour happens to main cause (68.8%) of their dissatisfaction. Regarding the Adequacy on the opportunity to enroll for post-graduation majority (47.9%) consider it to be inadequate. And also majorities (36.7%) are dissatisfied with their overall academic progression.  Study has revealed many ways by which employment status can be improvised and can be made more female friendly, by starting ‘Day-care’ services in every working institute. Also by improving work environment and living environment at peripheral areas, ensuring more safety and security. Academic engagement can be improved by making exam center more accessible and by providing wide range of training scope.Bangladesh Journal of Medical Education Vol.14(1) January 2023: 17-25